Сильная деформация анизотропных сред по плоскостям скольжения (конечно-разностное моделирование) - Мельникова Н. А. Наталья Александровна; Немирович-Данченко М. М. Михаил Михайлович; Чичинина Т. И. Татьяна Иннокентьевна; Элочж К. М. Э. Р. Кпата Мак Эгни Ричмонд; Алеева А. О. Анна Олеговна (2018, 2018)
Заглавие с экрана